Experimental and numerical investigation into temperature histories and residual stress distributions of high strength steel S690 welded H-sections. (15th June 2018) - Liu, Xiao; Chung, Kwok-Fai
Highlights: Four S690 welded H-sections were fabricated by two different welding processes. Surface temperature histories were measured by thermocouples. Surface residual stress distributions were measured by the hole-drilling method. FE models could predict temperature and residual stresses with a high accuracy. Residual stresses in S690 sections are proportionally smaller than those in ECCS. Abstract: In order to exploit full structural benefits offered by high strength steel materials in construction, it is important to examine and quantify effects of welding on these steel materials for development of effective structural design. A systematic experimental and numerical investigation into thermal and mechanical responses in four S690 welded steel H-sections with different cross-sectional dimensions during and after welding was conducted. During welding, surface temperatures of the welded sections at specific locations in close vicinity of welding lines were measured continuously using thermocouples. After welding, surface residual stresses in these welded sections were measured using an established hole-drilling method. Based on codified data and measured temperatures, three-dimensional finite element models with thermomechanical coupled analyses were established to simulate heat transfer from a welding arc onto the welded sections. After a careful calibration of predicted surface temperature histories of these sections against measured data, both through-thickness temperature and residual stress distributions of these sections were obtained. Predicted and measured surface residual stresses at specific locations of these sections were found to be in a good agreement. Hence, accuracy of the proposed models in predicting temperature histories and residual stress distributions of these welded sections are established. Averaged through-thickness residual stresses are provided as representative residual stress patterns for these sections. It should be noted that the maximum residual stresses in these welded sections are proportionally smaller than those in S355 welded sections. Consequently, the proposed finite element models are demonstrated to be able to predict accurate temperature histories and residual stress distributions of S690 welded H-sections through thermomechanical coupled analyses. The proposed models will be readily employed to investigate welding-induced residual stresses in welded H-sections and I-sections of various steel grades and plate thicknesses with different welding parameters. Predicted residual stress patterns will then be employed for numerical investigation into (i) axial buckling behavior of slender columns made of S690 welded H-sections, and (ii) lateral torsional buckling of unrestrained beams made of S690 welded I-sections. These numerical investigations will be reported separately.